Dinamika Kinerja Keuangan: Pengaruh Profitabilitas, Leverage, dan Likuiditas Terhadap Laba Bersih Sektor Non-Primer - Ainun Nabila; Amir; Andi Arman (Scimadly Publishing, 2026)
This study analyzes the effect of profitability (ROA), leverage (DER), and liquidity (CR) on net income in non-primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for 2021–2024. Using a quantitative method with purposive sampling, this study obtained 44 observation data points and analyzed them using multiple linear regression. The partial test results (t-test) indicate that profitability has a positive and significant effect on net income, liquidity has a negative and significant effect, while leverage has no significant effect. Simultaneously, all three variables significantly affect net income with a coefficient of determination (R Square) of 42.5%, while the remaining 57.5% is influenced by other factors outside the research model. These findings highlight the importance of optimizing asset management efficiency and preventing idle cash to sustainably maximize net income performance.